The Essence of the Methods of Civic Education of Students in the Russian Modern Higher School - USENKOVA, EKATERINA (Journal of Education, Technology and Computer Science, 2018)
The article reveals the models, methods of students’ civic education in the modern higher school. The quintessence and value of the application of role modeling, case-stage, information labyrinth are analysed as well.